Pengaruh Motivasi Kerja dan Pelatihan Kerja Terhadap Kinerja Karyawan PT. Elisabeth Berkat Energi Palembang - Meisin; Tobari; Agusria, Lesi (PT Maju Malaqbi Makkarana, 2026)
This study aims to determine the effect of work motivation and job training on employee performance at PT. Elisabeth Berkat Energi Palembang, both simultaneously and partially. PT. Elisabeth Berkat Energi Palembang is a company engaged in the distribution and trade of Biosolar B30/High Speed Diesel fuel oil in Palembang City, South Sumatra. This study is associative in nature. The population in this study consisted of 113 employees, with a sample of 54 respondents drawn using the Cluster Sampling technique based on the Slovin formula with a 10% margin of error. The data used were primary and secondary data, with data collection methods including questionnaires, interviews, and documentation. The analysis techniques used were multiple linear regression, F-test, t-test, and coefficient of determination. The results of the multiple linear regression analysis produced the equation Y = 5.069 + 0.459X₁ + 0.285X₂, which shows that work motivation and job training have a positive effect on employee performance. The F test results show an Fhitung value of 45.488 > ftabel of 2.41 with a significance of 0.000 < 0.1, indicating that there is a significant simultaneous effect of work motivation and job training on the performance of PT. Elisabeth Berkat Energi Palembang employees. The t test results show that there is a significant effect of work motivation on employee performance with a tCount value of 5.405 > ttable 1.675 (sig. 0.000 < 0.1), and there is a significant effect of job training on employee performance with a tCount value of 5.132 > ttable 1.675 (sig. 0.000 < 0.1). The coefficient of determination results show that the contribution of work motivation and job training to employee performance is 0.627 or 62.7%.